2021
DOI: 10.31234/osf.io/fc8n6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The reasonable, the rational, and the good: On folk theories and flexible use of different concepts of good judgment.

Abstract: We explore folk theories of sound judgment across two cultures, with a particular focus on the distinction between rationality and reasonableness and how people apply these concepts in a range of social and non-social contexts. Four studies using English-speaking samples in North America (Studies 1-3; N=1,826) and a Mandarin-speaking sample in China (Study 4; N=659) examine spontaneous descriptions of characteristics of sound judgment, preferences for and perception of agents in different social contexts (vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…This argument assumed that the definitions of theorists and of laypeople are equivalent, which is not necessarily so. Lay people define rationality as reductionist and seeking to serve a single value whereas they define reasonableness as holistic and seeking to balance incommensurable values (Meyers, Eibach, Hanxiao, & Grossmann, 2022). The lay definition of rationality does not require probabilities to be assigned, sidestepping the original rejection of rationality as a benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…This argument assumed that the definitions of theorists and of laypeople are equivalent, which is not necessarily so. Lay people define rationality as reductionist and seeking to serve a single value whereas they define reasonableness as holistic and seeking to balance incommensurable values (Meyers, Eibach, Hanxiao, & Grossmann, 2022). The lay definition of rationality does not require probabilities to be assigned, sidestepping the original rejection of rationality as a benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, more recent evidence with larger samples showed that Western Europeans also emphasize socio-emotional characteristics (Glück & Bluck, 2011). Moreover, work on folk understanding of reasonableness, a common synonym of wisdom, shows that in many non-Western countries such as China, or Pakistan, a reasonable person imbues both social and epistemic characteristics (Grossmann et al, 2020a;Grossmann & Eibach, 2021;Meyers et al, 2021). Overall, despite good reasons to expect cultural differences and lack of alignment between scientific and folk views of wisdom, empirical evidence on the salience of epistemic versus social characteristics for wisdom in non-Western societies remains inconclusive.…”
Section: Role Of Epistemics For Understanding Of Wisdom Beyond Weird ...mentioning
confidence: 99%
“…This argument assumed that the definitions of theorists and of laypeople are equivalent, which is not necessarily so. Lay people define rationality as reductionist and seeking to serve a single value whereas they define reasonableness as holistic and seeking to balance incommensurable values (Meyers, Eibach, Hanxiao, & Grossmann, 2022). The lay definition of rationality does not require probabilities to be assigned, sidestepping the original rejection of rationality as a benchmark.…”
Section: Introductionmentioning
confidence: 99%